Pipe scales and biofilms in drinking-water distribution systems: undermining finished water quality - Andra, Syam S.; Makris, Konstantinos C.; Botsaris, George (My University, 2014)
Safety and security are two important features of urban drinking-water distribution systems (UDWDS), worldwide, that are often compromised by a suite of physical, hydraulic, and chemical factors adversely impacting quality of potable water reaching consumer taps. Growth of scales and biofilm conglomerates (SBC) coupled with sorption of water chemicals and planktonic microorganisms by SBC has been increasingly recognized as underestimated contaminant sources in aging pipe networks of UDWDS. The main objective of this study was to provide an updated review of factors and processes associated with the increasing frequency of deteriorated finished water quality incidences as a result of SBC effects in UDWDS. This critical review integrated scattered knowledge on the effects of either pipe scales or pipe-anchored biofilm systems on contaminant destabilization and subsequent release into water. It was emphasized that little information exists on combined or concomitantly studied effects of SBC on finished water quality. Important synergistic SBC effects on finished water quality were identified as: (i) those promoting chemical release from pipe scales due to biofilm-induced alterations at the pipe surface/water interface, (ii) the synergistic SBC action on promoting increased release rates of pathogens or toxic chemicals into water, and (iii) the microbially enhanced corrosive phenomena on pipe scales and their constituents. Substantial room for improvement is anticipated for the water and global health research agenda by formulating innovative hypotheses and research designs that water authorities could benefit from as they strive towards further securing access to safe water in urban settings.
Keywords: Biofilms; Drinking water; Environmental health; Exposure; Pipe scales; Urbanization